Concurrent acute appendicitis and ileocolic intussusception in a 1-year-old child - Marjon, Lauren (Radiol Case Rep, 2018)
Intussusception and acute appendicitis are part of a differential diagnosis for acute abdominal pain and vomiting in the pediatric population. We describe a unique case combining appendiceal intussusception with concurrent acute appendicitis, or “appendi-sception.” A 1-year-old boy presented with 1 day of fussiness, vomiting, and red, gelatinous stool. Initial diagnosis on ultrasound was a routine ileocolic intussusception with nonvisualization of the appendix. However, after a failed air enema decompression, the patient was taken to the operating room where the appendix was discovered to be inflamed within the intussusceptum. This case is unique as few cases of both conditions occurring simultaneously have been previously described. It is important for radiologists to be aware of this combination of diagnoses as both require urgent evaluation and prompt treatment.